Unveiling Workplace Dynamics: The Impact of Supervisor Support on Job Satisfaction and Turnover Intention - Jafri Nurhamsyah Said; Muzakki Muzakki (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research investigates the impact of supervisor support on job satisfaction and turnover intention in the workplace. Supervisor support is considered a key factor in creating a positive work environment and motivating employees. The study involves the analysis of direct effects of supervisor support on job satisfaction and its influence on employee turnover intention. The research methodology includes surveys and data analysis from respondents PT. Polywood Industry Sinar Wijaya Surabaya. Statistical analysis results show a positive relationship between supervisor support and employee job satisfaction. These findings illustrate that supervisors who provide effective support tend to enhance employee job satisfaction in the workplace. Furthermore, the study explores the mediating role of job satisfaction in the relationship between supervisor support and employee turnover intention. Mediation analysis results indicate that job satisfaction partially mediates the positive impact of supervisor support on turnover intention. This suggests that through the enhancement of job satisfaction, supervisor support can effectively reduce employees' desire to quit their jobs. In conclusion, these findings imply the crucial role of supervisor support in increasing employee job satisfaction and reducing turnover intention. The practical implications of this research suggest that organizations can enhance efforts to improve supervisor support as a strategy to minimize turnover intention and enhance employee job satisfactionThe study provides in-depth insights into the dynamic how support from supervisors affects job satisfaction and the desire to leave the company in today’s modern work environment.